2022
DOI: 10.1038/s41392-022-01110-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulated cell death (RCD) in cancer: key pathways and targeted therapies

Abstract: Regulated cell death (RCD), also well-known as programmed cell death (PCD), refers to the form of cell death that can be regulated by a variety of biomacromolecules, which is distinctive from accidental cell death (ACD). Accumulating evidence has revealed that RCD subroutines are the key features of tumorigenesis, which may ultimately lead to the establishment of different potential therapeutic strategies. Hitherto, targeting the subroutines of RCD with pharmacological small-molecule compounds has been emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
154
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(220 citation statements)
references
References 487 publications
1
154
0
Order By: Relevance
“…RCD, or the cell suicide pathway, plays a critical role in organismal development and homeostasis. The most prominent and well-defined form of RCD is apoptosis, which serves as a defense mechanism against the emergence of cancer cells [ 4 ] and serves as a homeostatic mechanism to maintain cell populations in tissues [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…RCD, or the cell suicide pathway, plays a critical role in organismal development and homeostasis. The most prominent and well-defined form of RCD is apoptosis, which serves as a defense mechanism against the emergence of cancer cells [ 4 ] and serves as a homeostatic mechanism to maintain cell populations in tissues [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a PubMed search for ‘necroptosis and cancer’ and found that the number of articles in 2021 was the highest and continued to increase. A high-quality review published in August 2022 by Peng et al illustrates the important role of various programmed cell death pathways in cancer, including necroptosis ( Peng et al, 2022 ). Necroptosis follows signal regulation within tumor cells, and after TNF-α binds to TNFR1 on the plasma membrane, downstream protein molecules are recruited to form complex I ( Ofengeim and Yuan, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell death inducers have always been an important research field in cancer treatment strategies [ 843 ]. Mechanically, the available antitumor drugs induce cell cycle arrest or cell death unexceptionally.…”
Section: Introductionmentioning
confidence: 99%